Implementación de técnicas para el buen desarrollo de la motricidad fina en transversalidad con las diferentes áreas educativas (2020)
Currently, the field of education is being strongly influenced by globalization, in a world where technology is evolving more and more by leaps and bounds. For this reason, it is necessary to advance with it so as not to become obsolete in a traditional education. At the early childhood stage, children find in their bodies and movements the main ways to get in touch with the reality that surrounds them and, in this way, acquire the first knowledge about the world in which they are growing and developing. . Undoubtedly, the progressive discovery of the body as a source of sensations, the exploration of the possibilities of action and bodily functions, will constitute necessary experiences on which child thought will be built. Likewise, the affective relationships established in situations of motor activity, and in particular through play, will be fundamental for emotional growth. In this order of ideas, the child develops in his context, the influence of globalization and the intended situations according to his needs, satisfactions and emotions. This progress has generated changes in the way education is developed, implementing new pedagogical techniques and introducing new technologies to the educational field, which has awakened in the student community, all its capacity to manage virtual media inside and outside of it with great ease, which is satisfactory for the teaching community, to see all the possibilities that these new strategies offer for the teaching-learning process.